The Effectiveness of Acceptance and Commitment Therapy (ACT) on Disease Perception and Adherence to Treatment AmongPatients with Multiple Sclerosis - Sami, Puran; Emamipoor, Suzan; Rafiepoor, Amin (International Journal of Applied Behavioral Sciences, 2021)
Introduction:Multiple sclerosis is a common disease of the central nervous system. The aim of this study was to determine the effectiveness of acceptance and commitment therapy (ACT) on illness perception and adherence to treatment among patients with multiple sclerosis.Method:The present study was a quasi-experimental with pretest and posttest design. The statistical population of this study were all patients with multiple sclerosis under the auspices of the MS Society of Tehran in 2019. Forty-five women with multiple sclerosis were purposefully selected and randomly divided into two groups: acceptance and commitment therapy (n=15) and control group (n=15). Data were obtained with the revised illness perception questionnaire (IPQ-R) and the multiple sclerosis treatment adherence questionnaire (MS-TAQ). The repeated measurement analysis of variance and SPSS.22 software were used to analyze data.Result: The results showed that the acceptance and commitment therapy was effective on illness perceptions (p<0.001) and adherence to treatment (p<0.001). Conclusion: It can be concluded that effectiveness of acceptance and commitment therapy focus more on the outcome of the thought or how the person relates to their thoughts rather than on the content of the thought or attempt to eliminate it.Declaration of Interest: None